HPV Immunization in High School Student-Athletes Receiving Preparticipation Physical Evaluations at Mass Event Versus Other Venues - Cunningham, Andrew K. (Sports Health, 2020)
BACKGROUND: The preparticipation physical evaluation (PPE) is a requirement for high school sport participation in most states, but its location and role in preventive health care for adolescents is often questioned. HYPOTHESIS: Athletes who had their PPE performed in an office setting, in particular) by their primary care physician (PCP), will have higher human papillomavirus (HPV) immunization rates than those who had their PPE done in a group setting at a mass-participation PPE. STUDY DESIGN: Retrospective cohort study. LEVEL OF EVIDENCE: Level 3. METHODS: The PPE forms and immunization records for athletes at a single high school were reviewed to determine the location of PPE, the signing practitioner, and HPV immunization status. RESULTS: A total of 488 athletes (286 males, 202 females) were included; 51% had received at least 1 dose of the HPV vaccine while 39% had completed the series. There was no significant difference in vaccination rates between examination in an office setting versus a group setting. Athletes receiving their PPE at an urgent care facility had significantly lower rates of HPV series completion than all other settings (29% vs 43%; P = 0.004). PPE completion by the athlete’s PCP was associated with higher rates of vaccine series completion (46% vs 34%; P = 0.014). CONCLUSION: Athletes who completed their PPE in mass event and office-based settings had similar rates of HPV vaccine series initiation and completion. PPEs done at urgent care facilities were associated with low rates of vaccine series completion, while those done by a PCP were associated with higher rates. CLINICAL RELEVANCE: HPV immunization rates in athletes are low, and the PPE represents a potential opportunity to improve immunization rates.